Structural and magnetic properties of the layered perovskite system Sr2−xPrxCoO4 (x = 0.7, 0.9, 1.1). (April 2021) - Mukherjee, Rajarshi; Dan, Shovan; Mukherjee, S.; Ranganathan, R.
Abstract: We report the detailed structural and temperature dependent magnetic properties of well characterized, polycrystalline samples of Sr2− x Pr x CoO4 ( x = 0.7, 0.9, 1.1), in the temperature range 5 K–300 K. In Sr2− x Pr x CoO4 (0.7 ≤ x ≤ 1.1), short range or long range ferromagnetic (FM) order appears below T C 150 K. In general the low temperature magnetic state is a mixture of FM, paramagnetic (PM) and antiferromagnetic (AFM) matrices. The spin glass phase (SG) is observed in Sr1.1 Pr0.9 CoO4 below T f = 15 K due to comparable strengths of FM and AFM interactions. With increasing x, the Jahn-Teller distortion weakens the FM interaction and AFM interaction starts dominating. Isothermal remanent magnetization (IRM) as a function of time ( t ) shows that the relaxation mechanism is associated with the interfaces between different types of magnetic matrices. Graphical abstract: Image 1 Highlights: Sr2- x Pr x CoO4 (0.7≤ x ≤ 1.1) is a phase separated system. Below T C, it contains FM phase within AFM and PM matrices. Below T f, Sr1.1 Pr0.9 CoO4 consists of a spin glass phase. With increasing x, the Jahn-Teller distortion weakens the FM interaction. Below T C, IRM relaxes in an identical way for all three samples (0.7≤ x ≤ 1.1).